2022
DOI: 10.3390/met12020266
|View full text |Cite
|
Sign up to set email alerts
|

Al-Mn Intermetallics in High Pressure Die Cast AZ91 and Direct Chill Cast AZ80

Abstract: Manganese-bearing intermetallic compounds (IMCs) are important for ensuring adequate corrosion performance of magnesium-aluminium alloys and can be deleterious to mechanical performance if they are large and/or form clusters. Here, we explore the formation of Al-Mn IMCs in Mg-9Al-0.7Zn-0.2Mn produced by two industrial casting processes, high-pressure die casting (HPDC) and direct chill (DC) casting. As Al8Mn5 starts forming above the α-Mg liquidus temperature in this alloy, we consider its formation during mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…The 0.2 wt% Mn addition reacts with Al and impurity Fe to form Al-Mn-Fe intermetallics [38][39][40], starting at temperatures above the α-Mg liquidus and continuing throughout the solidification sequence including during the main eutectic reaction involving Mg 17 Al 12 [41][42][43][44]. Nave [24] found that a 0.3 wt% Mn addition had no significant effect on the eutectic morphology in AZ91, and a recent 3D imaging study on Al 8 Mn 5 in high pressure die cast AZ91 [45] found some Al-Mn particles in contact with Mg 17 Al 12 but the majority were surrounded by α-Mg.…”
Section: Introductionmentioning
confidence: 99%
“…The 0.2 wt% Mn addition reacts with Al and impurity Fe to form Al-Mn-Fe intermetallics [38][39][40], starting at temperatures above the α-Mg liquidus and continuing throughout the solidification sequence including during the main eutectic reaction involving Mg 17 Al 12 [41][42][43][44]. Nave [24] found that a 0.3 wt% Mn addition had no significant effect on the eutectic morphology in AZ91, and a recent 3D imaging study on Al 8 Mn 5 in high pressure die cast AZ91 [45] found some Al-Mn particles in contact with Mg 17 Al 12 but the majority were surrounded by α-Mg.…”
Section: Introductionmentioning
confidence: 99%